2015
DOI: 10.1007/s00192-015-2854-y
|View full text |Cite
|
Sign up to set email alerts
|

Post-void residual urine under 150 ml does not exclude voiding dysfunction in women

Abstract: Patients with voiding dysfunction often have normal PVR and so PVR < 150 ml cannot exclude voiding dysfunction. All patients should be evaluated using free flow measurements along with PVR to obtain a reliable, objective measurement of their voiding pattern, before anti-incontinence surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…However, the normal ranges are not agreed upon and moreover, limited as a low Qmax could also be due to BOO, whilst a low pdet@Qmax might be related to reduced outlet resistance, in the case of women with SUI. Moreover, it is possible to have DU and normal or low PVR, as recently demonstrated by Khayyami and colleagues in a small retrospective study on 20 women with voiding dysfunction [19].…”
Section: Diagnosismentioning
confidence: 79%
“…However, the normal ranges are not agreed upon and moreover, limited as a low Qmax could also be due to BOO, whilst a low pdet@Qmax might be related to reduced outlet resistance, in the case of women with SUI. Moreover, it is possible to have DU and normal or low PVR, as recently demonstrated by Khayyami and colleagues in a small retrospective study on 20 women with voiding dysfunction [19].…”
Section: Diagnosismentioning
confidence: 79%
“…The current cut-off values for covert PUR are rather arbitrary until data on the clinical consequences of abnormal PVR are available [ 16 ]. The arbitrary cut-off of 150 ml in nonpregnant women does not exclude voiding dysfunction [ 40 ]. The Agency Health Care Research and Quality guidelines define a PVR of less than 50 ml as being indicative of adequate emptying and a PVR of more than 200 ml as inadequate emptying [ 37 ], but the range between 50 and 200 ml remains ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, Khayyami et al highlighted that postvoid residual urine (PVR) alone cannot exclude preoperative voiding dysfunctions underlining the role of flow measurements before surgery. 16 Although in an uncomplicated population of women with SUI, it is not demonstrated that preoperative UDS can improve the outcome of continence surgery, UDS may provide additional information when the simple office-based evaluation is not enough to identify some relevant diagnosis such as voiding dysfunction in absence of a significant post voiding residual urine, or an 'asymptomatic' DO, or a urethral sphincter deficiency. 7 As of de novo OAB, it is a known complication of mid-urethral sling surgery for the treatment of SUI.…”
Section: Discussionmentioning
confidence: 99%